Practices and diversities in plexus and peripheral nerve blocks: A survey - Neha Singh; Vrushali Ponde; Balavenkatasubramanian Jagannathan; Gaurav Agarwal; Ritesh Roy; Amit Dixit (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Regional anesthesia plays a crucial role in perioperative medicine, influencing both immediate and long-term outcomes. However, there is a lack of data regarding the utilization and practices of plexus and peripheral nerve blocks. We attempted to investigate the practices of plexus and peripheral nerve blocks using a validated questionnaire. Material and Methods: A questionnaire was validated by 14 experts and was distributed online for the response. There were 1020 responses, and the data are expressed as frequencies and percentages. There were 58.2% females and 41.8% males, including 32.3% of the respondents with more than 20 years of experience and 27.5% having 10–20 years of experience. Participants from teaching hospitals, government, and private college comprised 49.7%, while those from the corporates and private practitioners constituted 50.2%. Results: Most participants fell into the age range of 31–40 years, followed by 41–50 years. The regional blocks were performed daily by 21.8%, weekly by 23.8%, every 15 days by 38.4%, and monthly by 16% of the participants. Furthermore, 43.6% of the participants discussed the block plan with the patients. The most common blocks of the upper limb and lower limb were the supraclavicular approach of the brachial plexus block (90.8%) and the fascia iliaca (82.5%), respectively. Conclusions: The present survey highlights the details about the present practices, advantages, and limiting factors for using plexus and peripheral nerve blocks. This is the first data acquired with a validated survey from a South Asian Country, which can be used to compare changes in future practices.